Hypothesis Testing With Proteomics: A Case Study Using Wound Healing Mechanisms in Fluids Associated With Barnacle Glue - Essock-Burns, Tara; Soderblom, Erik J.; Orihuela, Beatriz; Moseley, M. Arthur; Rittschof, Daniel (Frontiers in Marine Science, 2019)
Growth, molting, and hardening cuticle are intertwined processes for arthropods and share common protein systems to execute these functions. For barnacles, these processes are also tied to adhesion, which is vital to their survival and under great selection pressure. Unlike other crustaceans, barnacle growth, deposition of adhesive material and the curing of glue and cuticle, though associated, are spatially distinct from molting and occur at the interface of the calcareous baseplate and substrata. Here, we use an ancient system, the innate immune response as context and use proteomics and enzyme activity assays to test the hypothesis that chemistries associated with barnacle fluids and glue curing have their origins in wound healing and the innate immune response. Glue precursor material was extracted from barnacles and manipulated to accelerate known trypsin activity, curing, and the effects of sequential sampling. Using non-trypsin digests and searching for tryptic peptides, new products of endogenous trypsin were detected. We found extensive evidence of a prophenoloxidase system, including activating factors, serine proteases, and serine protease inhibitors. Through enzyme-specific substrate assays, phenoloxidase-like activity was found in glue and at the periphery of the base. The enzymatic nature of the phenoloxidase-like activity was confirmed through chemical inhibition and through heating the glue material to denature the enzyme. Further evidence for antimicrobial activity mediated by reactive oxygen species previously described during larval settlement and metamorphosis was the presence of peroxidases in glue precursor material. Beyond clotting, numerous extracellular matrix proteins were identified, suggesting glue curing may lead to stabilization of the initial clot and wound repair. We propose a model of the emerging hypothesis and find exciting potential for further testing innate immune components in this evolutionary approach to barnacle glue curing.